Bacteria of long skirts - McCoy, Nellie Reeder (My University, 1905)
Introduction: Bacteria are very small plants, which can be seen separately only.by the use of a high power microscope. The Science of Bacteriology teaches that these micro-organisms are present abundantly practically everywhere, in the air, water, food, soil and dust, in decaying organic matter, both vegetable and animal, and even within the tissues and fluids of the living body of diseased persons and animals. In fact it is from the presence of these minute germs, usually, that the disease is caused. To be sure not all bacteria are disease producing or "pathogenic, as those which produce disease are called; but it is the disease producing varieties in which the human body is especially interested. We could hardly get along without bacteria in the world, but we could do without very nicely, those which are producers of sickness and disease. How are we to rid the world of these harmful disease-producing bacteria? We may not be able to destroy them, but we can at least contribute our share to the elimination of disease, by being careful and cleanly in our habits. The conditions favorable for the growth and multiplication of bacteria are warmth, darkness and moisture. In the body all these conditions are found; this is the reason they multiply so rapidly unless the individual's health is so perfect that the body is able to withstand and throw off these germs. But to come back to my subject of skirts and the harm they produce. As it is, the habits of the Americans are generally very careless. As proof of this we need only to go along some mainly traveled street or pass some corner where crowds of men and boys congregate to note the filth of sputum from careless expectorations on the sidewalk.
Citation: McCoy, Nellie Reeder. Bacteria of long skirts. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Bact. AEgyptium; B. Arborescens; Bact. Crinatum; B. Zenkeri or Proteus Zenkeri; Theses